RT‐PCR in the early detection and monitoring of pathogen residual status in neonatal bacterial meningitis - Ying Li; Ruiqi Xiao; Peicen Zou; Yue Du; Qinglin Lu; Jun Cui; Yajuan Wang (iLabmed)
Abstract Background Early identification of pathogenic bacteria and monitoring residual status are essential for accurate treatment of neonatal bacterial meningitis (NBM). Methods Clinical data and specimens were collected from neonates with NBM. Bacterial cultures and RT‐PCR of blood and cerebrospinal fluid (CSF) were compared to assess the positivity rate, sensitivity and specificity of each method. Results RT‐PCR had a higher positivity rate compared with cultures, regardless of whether antibiotics had been used prior to specimen collection. After 1 week of regular antibiotic treatment, the number of pathogen DNA copy numbers in CSF was either undetectable or significantly reduced compared with previous levels. Conclusions RT‐PCR is expected to provide a basis for the precise application of antibiotics and the course of treatment for NBM, particularly in patients with negative cultures or those who have already been treated with antibiotics.